Thermal sprayed coatings and their tribological performances - Roy, Manish, 1964-; Davim, J. Paulo (Research essentials., 2015)
"This book showcases the latest research surrounding the development and use of thermal spraying techniques as well as the benefits of using thermal sprayed coatings in the industrial sector, focusing on practical solutions that can be applied to real-world settings"--